Subject dispersion of LIS research in Pakistan - Naseer, Mirza Muhammad; Mahmood, Khalid (Library & information science research, 2014)
A subject analysis of 5195 publications in library and information science (LIS) research in Pakistan over a period of 62years revealed that the majority of Pakistani LIS research focused on a few subject areas. Pakistani LIS researchers gave little attention to many subjects and completely ignored others. More than a quarter (26.72%) of the total items focused on “information treatment for information services” while 22% were related to “libraries as physical collections.” Other areas with some attention included “industry, profession and education” (12.32%) and “theoretical and general aspects of libraries and information” (11.40%). Researchers paid little attention to “housing technologies,” “technical services in libraries, archives and museums,” and “management.” •Pakistani library and information science research publications over the past 62years reveal a narrow subject dispersion.•Some subjects (e.g., intellectual freedom and censorship) are ignored, even in periods of democratic rule.•Information and library technology is a new area of research for library and information science in Pakistan.